Comparative study of lameness in crossbred cows on sand and pucca floor - SINGH, SUSHIL KUMAR; LATHWAL, S S; KASWAN, SANDEEP; DEVI, INDU (The Indian Journal of Animal Sciences, 2017)
A total of 40 (20 normal and 20 lame) lactating crossbred Karan Fries cows were randomly divided, considering their age, stage of lactation and parity, into four equal groups so as to rear on sand and pucca floor. Therefore, each group of sand and pucca floor included 10 normal and 10 lame cows for comparative study. All the lactating cows were recorded for milk fat %, rumen pH and lying time at fortnightly interval to find out existence of any kind of association with lameness. Parameters were recorded from each animal at fortnightly interval for duration of four months. Locomotion score of all the animals was recorded by visual examination of posture and gait of cows. Rumen pH was significantly (P<0.01) lower in lame KF cows in comparison to normal (non-lame) cows irrespective of type of floor. Similarly, locomotion score differed significantly (P<0.01) between lame and normal KF cows on both the floors. There was no significant difference with respect to milk fat percentage and lying time between lame and normal group of cows on both the floors. However, cows on sand floor showed significantly (P<0.01) higher lying time as compared to cows on pucca floor. Lower ruminal pH in lame cows could be one of the possible reasons for other complications related to lameness in lactating cows. Hence, soft bedding and diet management can be recommended for efficient management of crossbred lactating dairy animals with respect to hoof related problems.